2001
DOI: 10.1021/cm000766y
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Various Ordered Films of Oxotitanium(IV) Phthalocyanine by Vacuum Deposition and Their Spectroscopic Behavior

Abstract: Different types of ordered solid films of oxotitanium(IV) phthalocyanine (OTiPc) were grown in 50−500 nm thickness by vacuum deposition onto such conventional substrates as metal- and ITO-coated glass and neat glass at a rate of ∼0.05 nm s-1. Under 10-3−10-4 Pa isotropic films with short-range molecular organization and preferential molecular orientation were grown on the substrates kept at ∼25 °C but ordered α (phase II) or β (phase I) crystal films on the substrates heated at 150 °C. The deposition onto surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
73
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 41 publications
6
73
1
Order By: Relevance
“…More complicated XRD peaks appeared at 150°C, in which the diffraction peaks at 7.5°, 12.5°, 25.3°, and 28.6°were assigned to a-phase and the diffraction peak at 26.2°was belonged to b-phase. [18][19][20] It was further confirmed from the XRD results that the vacuum deposited films of TiOPc on pure Si/SiO 2 surface were in amorphous or in mixed-phases states, which were consistent with the UV-NIR results. Yonehara and Brinkmann et al [18][19][20] found surface modifications of substrates with organic thin layers exerted remarkable effects on the molecular alignment of vacuum deposited TiOPc films.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…More complicated XRD peaks appeared at 150°C, in which the diffraction peaks at 7.5°, 12.5°, 25.3°, and 28.6°were assigned to a-phase and the diffraction peak at 26.2°was belonged to b-phase. [18][19][20] It was further confirmed from the XRD results that the vacuum deposited films of TiOPc on pure Si/SiO 2 surface were in amorphous or in mixed-phases states, which were consistent with the UV-NIR results. Yonehara and Brinkmann et al [18][19][20] found surface modifications of substrates with organic thin layers exerted remarkable effects on the molecular alignment of vacuum deposited TiOPc films.…”
supporting
confidence: 81%
“…[18][19][20] It was further confirmed from the XRD results that the vacuum deposited films of TiOPc on pure Si/SiO 2 surface were in amorphous or in mixed-phases states, which were consistent with the UV-NIR results. Yonehara and Brinkmann et al [18][19][20] found surface modifications of substrates with organic thin layers exerted remarkable effects on the molecular alignment of vacuum deposited TiOPc films. A highly ordered a-TiOPc film with an "edgeon" molecular orientation was selectively grown on the surfaces of the gold substrate modified with a self-assembled monolayer of octadecanethiol.…”
supporting
confidence: 81%
See 3 more Smart Citations